Neurotoxic and respiratory effects of human use drugs on a Neotropical fish species, Phalloceros harpagos - de Oliveira Dos Santos, Paula Rodrigues (2022)
Pharmaceutical drugs are usually and continuously carried to the aquatic environment in different ways. Thus, they are pseudo-persistent in the environment, and they may exert deleterious effects on aquatic organisms. The objective of the present study was to investigate the acute and chronic effects of two widely used pharmaceutical drugs, paracetamol (analgesic and antipyretic) and propranolol (β-blocker) on the activity of specific biomarkers (namely cholinesterase enzymes and lactate dehydrogenase) of the neotropical fish Phalloceros harpagos. The obtained results indicate an inhibition of the activity of the enzyme lactate dehydrogenase (LDH) after acute exposure to paracetamol, and an increase in cholinesterase activity in acutely propranolol-exposed fish. Chronic exposure to both drugs did not modify the enzymatic activities. Such short-term changes in enzymatic activities may be harmful to organisms, altering the preferential pathway of energy metabolism, and may induce behavioral changes that may compromise prey capture and predator escape, and in the longer term may induce population declines.